Sintonia adaptativa de algoritmos de controle de potência PID em redes ópticas passivas de próxima geração baseada em inteligência computacional - Santos, Layhon Roberto Rodrigues dos (2018)
In this work, is it proposed some power control strategies with adaptive auto-tuning for a distributed power control algorithms (DPCAs) proportional-integral-derivative (PID) using intelligent systems (IS): i) the Tyreus-Lyuben (TL) method; ii) particle swarm optimization (PSO); and iii) Adaline artificial neural network (AANN). The power control approach is realized for the upstream of next-generation passive optical networks (NGPON), especially to be deployed in the context of optical code division multiplexing access passive networks (OCDMA-PON). The main results demonstrate the ability of control and adaptive auto-tuning through of the TL, PSO and AANN methods considering realistic error estimates in the optical channel. The advantages and disadvantages of each method and its variations are evaluated.